Kosmos : jewellery, adornment and textiles in the Aegean Bronze Age - International Aegean Conference (13th 2010 University of Copenhagen); Nosch; Laffineur, Marie-Louise, Robert (Leuven: Peeters, 2012)
Containing the complete proceedings of the 13th International Aegean Conference, this is almost certainly the biggest book on Bronze Age clothing and jewellery that you are ever likely to see. Nearly 100 papers address a vast array of topics including textile production, costumes, dyes and pigments, colours, jewellery, aesthetics, body adornment, luxury and exotic items, gender and femininity/masculinity, as well as their social, religious, ideological, economic, technological, administrative and philological connections.
Includes bibliographical references.
Keywords: Jewelry, Ancient -- Congresses. -- Greece; Jewelry, Ancient -- Congresses. -- Turkey; Costume -- History -- Congresses. -- To 500 -- Greece; Costume -- History -- Congresses. -- To 500 -- Turkey; Textile fabrics, Ancient -- Greece -- Congresses; Textile fabrics, Ancient -- Turkey; Bronze age -- Congresses -- Aegean Sea Region; Prehistoric archaeology